Experimental Study on the Mechanical Properties of Sandstone under the Action of Chemical Erosion and Freeze-Thaw Cycles. (1st March 2021) - Cui, Lizhuang; Qin, Nan; Wang, Shuai; Feng, Xuezhi
Abstract : In order to study the mechanical properties of sandstone under the coupling action of chemical erosion and freeze-thaw cycles, the fine-grained yellow sandstone in a mining area in Zigong, China, is collected as the research object. The changes in mechanical properties of yellow sandstone under the coupling action of chemical solution erosion and freeze-thaw cycles are analyzed based on uniaxial compression tests (UCTs) and triaxial compression tests (TCTs). The results show that, with the increase in freeze-thaw cycles, the compressive strength, elastic modulus, and cohesion of the sandstone samples decrease with varying degrees. Under constant freeze-thaw cycles, the most serious mechanical properties of degradation are observed in acidic solution, followed by alkaline solution and neutral solution. Under different confining pressures, the compressive strength and elastic modulus of the sandstone samples decrease exponentially with the increase in freeze-thaw cycles. Under the action of the chemical solution erosion and freeze-thaw cycles, the internal friction angle fluctuates around 30°. For the cohesion degradation, 35.4%, 29.3%, and 27.2% degradation are observed under acidic, alkaline, and neutral solutions. Nuclear magnetic resonance imaging shows that the chemical erosion and freeze-thaw cycles both promote the degradation of rock properties from surface to interior; after 45 freeze-thaw cycles, the mechanical properties drop sharply. To properly design rock tunneling support and long-term protection in the cold region, the impact of both freeze-thaw cycles and chemical erosion should be considered.